Answer:c
c = - 15
Explanation:
Simplifying
19c + 31 = 26c + -74
Reorder the terms:
31 + 19c = 26c + -74
Reorder the terms:
31 + 19c = -74 + 26c
Solving
31 + 19c = -74 + 26c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-26c' to each side of the equation.
31 + 19c + -26c = -74 + 26c + -26c
Combine like terms: 19c + -26c = -7c
31 + -7c = -74 + 26c + -26c
Combine like terms: 26c + -26c = 0
31 + -7c = -74 + 0
31 + -7c = -74
Add '-31' to each side of the equation.
31 + -31 + -7c = -74 + -31
Combine like terms: 31 + -31 = 0
0 + -7c = -74 + -31
-7c = -74 + -31
Combine like terms: -74 + -31 = -105
-7c = -105
Divide each side by '-7'.
c = 15
Simplifying
c = - 15